(untitled) (Journal of the Sociology and Theory of Religion, 2012)
Natural communities, based on the existence of a minimal thought, expressed through religion, werethe only form of social organization until the English Revolution put the bases of an alternative form,the individual communities. The individual communities, grounded in the empowerment of theindividual, broke this minimal thought, facilitating the emergence of alternative thoughts inside thecommunity, making possible the scientific revolution and the participation of all in the sovereignty.As societies dynamic, in constant change, though they facilitate the search at liberty of thehappiness of everyone, they expose the individual to a lack of references, to the abyss of happiness.This means that in his own crib, the West, individual communities have been fought and lacking anuniversal power of attraction. Their survival, development and expansion determine the XXI Century